2017
DOI: 10.3847/1538-4357/835/1/61
|View full text |Cite
|
Sign up to set email alerts
|

Chromospherically Active Stars in the Rave Survey. Ii. Young Dwarfs in the Solar Neighborhood

Abstract: A large sample of over 38,000 chromospherically active candidate solar-like stars and cooler dwarfs from the RAVE survey is addressed in this paper. An improved activity identification with respect to the previous study was introduced to build a catalog of field stars in the solar neighborhood with an excess emission flux in the calcium infrared triplet wavelength region. The central result of this work is the calibration of the age-activity relation for main-sequence dwarfs in a range from a few 10 Myr up to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 64 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…This result is in agreement with all the works that studied the evolution of the level of magnetic activity vs. age (see e.g. Žerjal et al 2017;Oláh et al 2016, and references therein)…”
Section: Oláh Et Al (2016) Investigated How Thesupporting
confidence: 93%
“…This result is in agreement with all the works that studied the evolution of the level of magnetic activity vs. age (see e.g. Žerjal et al 2017;Oláh et al 2016, and references therein)…”
Section: Oláh Et Al (2016) Investigated How Thesupporting
confidence: 93%
“…Photospheric component of the flux was eliminated from the active candidates by subtracting the best-matching inactive template spectrum. The activity proxy used is the combined Equivalent Width (EW IRT ) of each calcium line in the spectrum of the star: EW IRT = EW 8498 + EW 8542 + EW 8662 (6) Zerjal et al (2017) found the distribution of EW IRT of inactive stars to be centred around −0.05Å with a σ=0.16Å and hence used 0.16Å as the activity detection limit. Subsequently, out of the 38678 candidate spectra they catalogued, they reported about 13,000 stars with activity level above 2σ and about 22,000 stars with activity above 1σ respectively.…”
Section: Variation Of Host Star Uv Activity With Planet Propertiesmentioning
confidence: 99%
“…UCAC4 544-056450 = TIC 307915958 The position on the color-period diagram is consistent with similar-color members of Group X, implying an age of about 300 Myr. 2MASS J16001203-0230594 = TIC 168457615 The activity and gravity indicators (Bowler et al 2019;Žerjal et al 2017), the lithium non-detection and the position in the CMD close to MS are consistent with an age of few hundreds Myr but we do not have a determination of rotation period to fully confirm and refine it. LSPM J1604+2331 = TIC 445889890 It is a M5 star.…”
Section: Discussionmentioning
confidence: 82%
“…There is no lithium to be seen in the archive FEROS spectrum we analyzed, as also found by Bowler et al (2019), indicating age older than about 100 Myr. High levels of chromospheric and coronal activity have been measured (Bowler et al 2019;Žerjal et al 2017). HD 34652 = TIC 317383399 We measured from TESS photometry a rotation period P= 1.753±0.026 d and a secondary period (of comparable power in both GLS and CLEAN periodograms) P= 1.527 d likely arising from surface differential rotation.…”
Section: Discussionmentioning
confidence: 91%